2023
DOI: 10.3390/en16073286
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Germanium-Decorated h-BN/MoS2 Heterostructure Nanosheets: An Advanced Electrocatalyst for Energy Storage Applications

Abstract: Increasing concerns about the vulnerability of the world’s energy supply and the necessity to implement sustainable technologies have prompted researchers to develop high-performance electrocatalysts that are affordable and efficient for converting and storing renewable energy. This article reports a facile approach to fabricating two-dimensional (2D) Ge-decorated h-BN/MoS2 heterostructure nanosheets by self-assembly for multiple electrochemical applications such as supercapacitor and hydrogen evolution reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…It was suggested that the electronic interaction between h‐BN and metal substrate played a significant role in modulating the electrocatalytic activity of these materials 152 . Additionally, B‐C‐N with tunable consistence showed greater potential in the field of catalytic water splitting than that of h‐BN 57,60,153 . Sun and coworkers discovered that cobalt phosphide and B‐C‐N hybridization (CoP/B‐N‐C) hold promise for HER in alkaline solution and seawater, with the overpotential of 154 and 545 mV at 10 mA cm −2 , respectively 154 .…”
Section: Applications In Electrochemical Energy Conversionmentioning
confidence: 99%
“…It was suggested that the electronic interaction between h‐BN and metal substrate played a significant role in modulating the electrocatalytic activity of these materials 152 . Additionally, B‐C‐N with tunable consistence showed greater potential in the field of catalytic water splitting than that of h‐BN 57,60,153 . Sun and coworkers discovered that cobalt phosphide and B‐C‐N hybridization (CoP/B‐N‐C) hold promise for HER in alkaline solution and seawater, with the overpotential of 154 and 545 mV at 10 mA cm −2 , respectively 154 .…”
Section: Applications In Electrochemical Energy Conversionmentioning
confidence: 99%